Bioethanol manufacturing from industrial olive pomace slurry through integrated hydrothermal carbonisation and non-conventional yeast-based fermentation processes - Adnan Asad Karim; Maria Lourdes Martínez-Cartas; Manuel Cuevas-Aranda (Energy Conversion and Management: X, 2025)
The two-phase olive pomace slurry (TOPS) is the major waste of the olive oil industry. Hydrothermal carbonisation (HTC) has been widely used for the conversion of TOPS into hydrochar, a solid biofuel. The HTC process also co-produces a liquid hydrolysate, whose valorisation has been scarcely investigated. This study focussed on to investigate the composition (reducing sugars, total phenols, acetic acid and furfural) and use of the hydrolysate derived from conventional and microwave assisted HTC of TOPS to produce bioethanol by the fermentation carried out by Hansenula polymorpha, a non-conventional yeast. On the basis of holocellulose content (39.12 %) present in dry TOPS, the optimum conditions to achieve a maximum reducing sugar yield of 25.92 % through conventional HTC were 180 °C and 30 min. In the case of microwave HTC, the optimal conditions were 203 °C and 30 min to obtain a maximum reducing sugar yield of 27.88 %. The HTC also produced total phenols (up to 3.30 %), acetic acid (up to 3.33 %), and furfural (up to 1.96 %). In comparison to conventional HTC, the microwave HTC advantage was generation of lower concentrations of fermentation inhibitors. The H. polymorpha strain produced maximum overall bioethanol yield of 0.21 g g−1 in case of fermentation of liquid hydrolysate at 45 °C with inoculum concentrations of 0.8 g dm−3. These findings emphasised that the HTC of TOPS could be an alternative and promising method for co-production of reducing sugars, bioethanol and total phenols.